2018
DOI: 10.1111/jfpp.13598
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction process of polysaccharides from Dendrobium officinale and evaluation of the in vivo immunmodulatory activity

Abstract: Dendrobium officinale (D. officinale) was regarded as the nutritious food in Asia for the remarkable bioactivities on immunmodulatory. Dendrobium officinale polysaccharide (DOP) served as the main active compound in the herb. Extraction of DOP was investigated and immunmodulatory activities were evaluated. The optimal extraction process (liquid‐to‐material ratio of 24.6:1, extraction time of 2.1 hr, and temperature of 67.4 °C) was obtained by single‐factor analysis and response surface optimization. Under this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Li et al [17] and Tang et al [18] showed that tea polysaccharides and purple sweet potato polysaccharides could regulate the immune system and intestinal microflora. Dendrobium officinale polysaccharides also had immunomodulatory activity as well as the potential for a promising dietary therapy for constipation in daily life [19,20]. Similarly, polysaccharide is one of the active components of M. halliana flowers, and our previous research proved that the polysaccharide of M. halliana flowers (MHFP) could effectively improve functional constipation [21].…”
Section: Introductionmentioning
confidence: 93%
“…Li et al [17] and Tang et al [18] showed that tea polysaccharides and purple sweet potato polysaccharides could regulate the immune system and intestinal microflora. Dendrobium officinale polysaccharides also had immunomodulatory activity as well as the potential for a promising dietary therapy for constipation in daily life [19,20]. Similarly, polysaccharide is one of the active components of M. halliana flowers, and our previous research proved that the polysaccharide of M. halliana flowers (MHFP) could effectively improve functional constipation [21].…”
Section: Introductionmentioning
confidence: 93%
“…Then, the ethanol is filtered and evaporated to dryness. Finally, the solid residue is extracted by different methods, for example hot water extraction ( 19 ), ultrasonic-assisted extraction ( 20 ), enzyme-assisted extraction ( 21 ), microwave-assisted extraction ( 22 ), supercritical fluid extraction ( 23 ), and freeze-thaw cold pressing ( 24 ).…”
Section: Extraction Isolation and Purification Methodsmentioning
confidence: 99%
“…In this case, today, herbal medicines are investigated for transdermal drug delivery systems. Polysaccharides extracted from herbs are of increasing interest due to their extensive range of pharmacological applications, including acting on antitumor, immunomodulatory, antioxidant, and anti-inflammatory [ 15 , 16 , 17 , 18 ].…”
Section: Polysaccharidementioning
confidence: 99%